Tafsir Ayat-Ayat al-Quran Berkenaan Penjagaan Alam Sekitar dan Analisis Isu-Isu Alam Sekitar di Malaysia: Interpretation of the Qur’anic Verses on Preservation of Environment and Analysis of Environmental Issues in Malaysia - Abdul Halim, ‘Imaaduddin; Mat Akhir, Noor Shakirah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
Nowadays, various environmental issues have been discussed which include its importance, destruction or the ways of preventing any environmental destruction. The current paper will explore these issues from both the conventional and the Islamic perspectives. Environmental distruction in the present time are becoming more common due to the uncontrolled exploitation of natural resources by human beings in order to generate profits. In view of the increasing of the technological advances in Malaysia presently, the above matter should not happen if people’s intellect is founded on faith. People are able to distinguish between positive and negative consequences of voraciously exploiting natural resources. However, the greed that engulfs some people, has obscured these people to think of the consequences in the future of their acts. From the Islamic perspective with the Quran as the ultimate reference, the environmental destruction could actually be prevented if individuals are aware of his or her trustworthiness or responsibility as His caliphate in the earth. The questions here, is there any particular verse in the Holy Quran that explains the environmental preservation? Is the teaching of the Holy Quran could provide solutions to the environmental crises in Malaysia? The current study provides explanations to the above questions based on the literature surveys and the content analysis method. The findings of the interpretation of the selected verses concerning the environmental preservation have identified that there are numerous verses in the Holy Qur'an which emphasize the concept of the preserving nature.